2020
DOI: 10.1101/2020.06.09.136473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

APhelipanche ramosaKAI2 Protein Perceives enzymatically Strigolactones and Isothiocyanates

Abstract: 22Phelipanche ramosa is an obligate root-parasitic weed threatening major crops in central 23Europe. For its germination, it has to perceive various structurally diverging host-exuded 24 signals, including isothiocyanates (ITCs) and strigolactones (SLs). However, the receptors 25 involved are still uncharacterized. Here, we identified five putative SL receptors in P. ramosa, 26 of which PrKAI2d3 is involved in seed germination stimulation. We established the high 27 plasticity of PrKAI2d3, allowing interaction… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…In addition, the affinity of the ligand–receptor relationship can be inferred using ITF measurements, in which ligand binding alters the tryptophan microenvironment and therefore the overall fluorescence properties of the protein (Ghisaidoobe & Chung, 2014). ITF measurements are only appropriate for ligands that do not interfere with a fluorescence signal from tryptophan, and ITF has been used elsewhere to infer a ligand‐binding relationship between strigolactone analogues such as GR24 and various D14 and KAI2 homologues (de Saint Germain et al ., 2016; de Saint Germain et al ., 2020). ITF data have also been documented as evidence for binding of KAR 1 by KAI2 (Toh et al ., 2014), but we contend that karrikins are incompatible with ITF assays because they absorb strongly at the same wavelengths (280–295 nm) that excite tryptophan (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the affinity of the ligand–receptor relationship can be inferred using ITF measurements, in which ligand binding alters the tryptophan microenvironment and therefore the overall fluorescence properties of the protein (Ghisaidoobe & Chung, 2014). ITF measurements are only appropriate for ligands that do not interfere with a fluorescence signal from tryptophan, and ITF has been used elsewhere to infer a ligand‐binding relationship between strigolactone analogues such as GR24 and various D14 and KAI2 homologues (de Saint Germain et al ., 2016; de Saint Germain et al ., 2020). ITF data have also been documented as evidence for binding of KAR 1 by KAI2 (Toh et al ., 2014), but we contend that karrikins are incompatible with ITF assays because they absorb strongly at the same wavelengths (280–295 nm) that excite tryptophan (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is conceivable that there exists an endogenous enzyme with strigolactone demethylase activity to generate KL. However, the preferred 2′( S ) stereochemistry of KAI2 ligands is opposite to that of natural strigolactones, and natural strigolactone‐like compounds with a desmethyl D‐ring have yet to be reported, even though such compounds are likely to be discovered by seed germination bioassays (de Saint Germain et al ., 2020). Furthermore, there has been evolutionary loss of key enzymes in strigolactone biosynthesis (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted November 24, 2020. ; https://doi.org/10.1101/2020.11.24.395954 doi: bioRxiv preprint Bythell-Douglas et al 2017), the expansion of the PpKAI2L family in P. patens (and not in other bryophytes such as Marchantia polymorpha, that contains two MpKAI2 genes), as in parasitic angiosperms Toh et al 2015), may have allowed the emergence of SL sensitivity (de Saint Germain et al 2020). Neofunctionalization of additional KAI2 copies in P. patens ancestry towards SL perception is therefore a possible explanation for our findings in this moss and would reveal a convergent evolution process, relative to the emergence of D14 in seed plants.…”
Section: Ppkai2l-j -G -M Mediate Ppccd8-derived (Sl-related) Responsesmentioning
confidence: 99%
“…The ageold question in receptor diversity has been the evolutionary purpose and functional significance of KAI2 duplication events. It has been shown that D14 and KAI2 are not able to complement each other functions in planta [37][38][39][40][41] . To this end, within the ligand binding site of KAI2 receptors the substitution of a few amino acids can alter ligand specificity between KAI2 duplicated copies 39,42 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, several crystal structures of KAI2/D14 receptors have been reported and have led to a greater understanding of receptor-ligand perception and the hydrolytic activity of the receptor towards certain ligands 11,12,19,31,36,38,[44][45][46][47][48][49][50][51] . The divergence between duplications of KAI2 receptors to confer altered ligand specificity has been partially addressed at the physiological and biochemical level for only few plant species, and a structural examination has been limited [38][39][40]42 .…”
Section: Introductionmentioning
confidence: 99%